1965
DOI: 10.1111/j.1365-2389.1965.tb01427.x
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Immobilization of Applied Phosphate in Relation to Soil Properties

Abstract: The fate of superphosphate applied at 500 and 1,000 Ib PzO, per acre in a field experiment with twenty-four sites was followed by measuring changes in the L-value over 5 years. The L-value decreased exponentially at a rate that was expressed as the time in years for half the applied phosphate to become non-labile (the half-life). The two fertilizer rates gave similar values in most of the experiments and half-life values were satisfactorily measured for nineteen soils ; the values ranged from I to 56 years.Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 3 publications
(1 reference statement)
0
27
0
1
Order By: Relevance
“…These results agree with much field trial evidence (Research Division, New Zealand Ministry of Agriculture and Fisheries unpublished data) showing that liming generally has no effect on the availability of P on yellow-brown loams. However, some depressions in available P because of liming occur on some trials on these soils in the presence but not in the absence of applied P. This may result from the formation of insoluble calcium phosphates (Larsen et al 1965) and it may also cause the depressions in plant P which occurred during some seasons in this experiment.…”
Section: Discussionmentioning
confidence: 90%
“…These results agree with much field trial evidence (Research Division, New Zealand Ministry of Agriculture and Fisheries unpublished data) showing that liming generally has no effect on the availability of P on yellow-brown loams. However, some depressions in available P because of liming occur on some trials on these soils in the presence but not in the absence of applied P. This may result from the formation of insoluble calcium phosphates (Larsen et al 1965) and it may also cause the depressions in plant P which occurred during some seasons in this experiment.…”
Section: Discussionmentioning
confidence: 90%
“…Calcium enhances the formation of basic calcium phosphate minerals that lower the concentration of phosphate in the water extract. Larsen et al (1965) suggested that the decrease in labile phosphate could be the result of the formation of a crystalline basic calcium phosphate at a rate that increases with increases in soil pH. In a column-leaching study, Nelson et al (1991) reduced the concentration of dissolved P by 88% in extracts from Alfisols with a sandy loam surface texture treated with gypsum.…”
Section: Nitrogen and Phosphorusmentioning
confidence: 96%
“…Although annual clover lime response trails under glasshouse conditions in NZ are scarce, a field trial by Lambert & Grant (1980) found that southern North Island hill country pasture legume vigour and soil P showed a positive response to low lime rate application (0Á3.5 t/ha), with a small negative response in legume vigour at higher lime rates. This effect has been attributed to the depression of P availability at high pH (!6.0) due to calcium phosphate formation (Larsen et al 1965), which may be the reason for yield depression at higher liming rates in the current experiment. Lambert & Grant (1980) found that legume Mo concentration increased in response to lime addition, which is in agreement with the results here (Table 4).…”
Section: S Responsementioning
confidence: 96%